SERVQUAL Based On Islamic Values: Member Satisfaction Model At BMT NU Cabang Purwoharjo - Safira Ardika Dwi Putri; Sindi Maya Urbach; Yunus Zamroji (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to analyze member satisfaction with savings services at the BMT NU Purwoharjo. A qualitative case study approach was used, with data collected through in-depth interviews, observations, and documentation involving active savings members. Results indicate overall member satisfaction, particularly regarding service accessibility, staff professionalism, transaction speed, and clarity of sharia contract information. SERVQUAL dimension analysis revealed that all five dimensions tangibles, reliability, responsiveness, assurance, and empathy contribute positively to member satisfaction. The integration of Islamic values ​​such as amanah (trustworthiness), fastabiqul khairat (competing in goodness), and rahmah (compassion) strengthens these service dimensions. In conclusion, improving service quality across all SERVQUAL dimensions, along with strengthening sharia compliance and community-based service innovation, is crucial to maintaining member satisfaction at the BMT NU Purwoharjo Branch. Keywords : Member satisfaction, service quality, Servqual, Islamic values, BMT